2011
DOI: 10.1111/j.1468-0327.2011.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Keynesian government spending multipliers and spillovers in the euro area

Abstract: 4Non-technical summary 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 67 publications
5
85
1
4
Order By: Relevance
“…While a consensus on positive short term effects of fiscal stimuli seems to have emerged (see Corsetti, Meier and Mueller, 2009;Cwik and Wieland, 2010;Coenen, Straub and Trabandt, 2011), there is evidence casting doubt on the conclusion that by symmetry, austerity in the presence of high debt levels has contractionary effects (Alesina and Ardagna, 2010;Cochrane, 2011;Corsetti et al, 2011). Earlier research on episodes of fiscal austerity found mixed evidence but emphasized the possibility of favourable outcomes (see Alesina and Drazen, 1991;Bertola and Drazen, 1991).…”
Section: Fiscal Policy: From Rules To Discretionmentioning
confidence: 98%
“…While a consensus on positive short term effects of fiscal stimuli seems to have emerged (see Corsetti, Meier and Mueller, 2009;Cwik and Wieland, 2010;Coenen, Straub and Trabandt, 2011), there is evidence casting doubt on the conclusion that by symmetry, austerity in the presence of high debt levels has contractionary effects (Alesina and Ardagna, 2010;Cochrane, 2011;Corsetti et al, 2011). Earlier research on episodes of fiscal austerity found mixed evidence but emphasized the possibility of favourable outcomes (see Alesina and Drazen, 1991;Bertola and Drazen, 1991).…”
Section: Fiscal Policy: From Rules To Discretionmentioning
confidence: 98%
“…A number of recent studies have indicated a sharp decline in spending and tax multipliers stemming from the recent financial crisis, providing some merit to crowding out effects (IMF, 2008;Égert, 2010;Wieland, 2010). Other studies seem to support prevalence of positive effects of fiscal spending on output in spite of the decline in the value of fiscal multipliers during the recent crisis (Cwik/Wieland, 2009;Corsetti, et al, 2009). Current econometric models for the U.S. estimate that a tax cut has a multiplier effect of about 1.0, while the multiplier effect for government spending is 1.6 after about 18 months (Romer, 2009).…”
Section: Literature Survey On Causal Interactions Between Macroecomentioning
confidence: 99%
“…6 In a monetary union that is open to the rest of the world, the inverse transmission is likely to involve the external exchange rate of the union, as pointed out above. Cwik/Wieland (2011) found this transmission channel at work in the euro area.…”
mentioning
confidence: 99%